Integrating Hakam and Court-Annexed Mediation: Strengthening Divorce Dispute Resolution in Indonesia's Religious Courts - Marhendi Marhendi; Aditya Eko Adrianto (Sultan Publisher, 2026)
Mediation in the settlement of divorce disputes in Indonesian Religious Court has been institutionalized through Supreme Court Regulation (PERMA) Number 1 of 2016. However, there are still significant challenges in the implementation as mediation tends to be a procedural requirement rather than an effective mechanism for reconciliation. This study aims to find out the normative basis of mediation in Islamic family law, evaluate the implementation of court annexed mediation in the Religious Courts in Indonesia, and find the institutional and normative gaps that affect the effectiveness of mediation. This research is normative legal research with a statutory, conceptual and doctrinal approach. Legal materials were collected by means of systematic review of primary, secondary and tertiary legal sources and analysed by the means of qualitative content analysis and normative legal interpretation. The results show that Islamic family law provides a comprehensive normative system through the principles of islah, hakam, and maqashid al-shariah, while court-annexed mediation remains largely procedural, resulting in a significant institutional gap between family-based reconciliation and judicial mediation. Following this, this study presents an Integrated Mediation Framework, which systematically integrates Islamic legal principles with court-annexed mediation to enhance divorce dispute resolution. The proposed model integrates Islamic legal principles, family participation, judicial supervision and professional mediation into a comprehensive model of dispute resolution. The framework is the main contribution of the study as it bridges classical Islamic family law with contemporary judicial mediation and provides practical guidance to improve mediation practice and judicial policy in Indonesia’s Religious Courts.